N-Glycosylation Site Analysis of Citrullinated Antigen-Specific B-Cell Receptors Indicates Alternative Selection Pathways During Autoreactive B-Cell Development - Vergroesen, Rochelle D.; Slot, Linda M.; van Schaik, Barbera D. C.; Koning, Marvyn T.; Rispens, Theo; van Kampen, Antoine H. C.; Toes, René E. M.; Scherer, Hans U. (Frontiers in Immunology, 2019)
Many autoimmune diseases are hallmarked by autoreactive B and plasma cell responses that are directly or indirectly involved in disease pathogenesis. These B-cell responses show large variability between diseases, both in terms of the secreted autoantibody repertoire and the dynamics and characteristics of the underlying B-cell responses. Hence, different mechanisms have been proposed to explain the emergence of autoreactive B cells in an otherwise self-tolerant immune system. Notably, most mechanistic insights have been obtained from murine studies using models harboring genetic modifications of B and T cells. Given recent technological advances that have rendered autoreactive human B cells accessible for analysis, we here discuss the phenomenon of extensive N-glycosylation of the B-cell receptor (BCR) variable domain of a prototypic human autoreactive B-cell response and its potential role in the generation of autoimmunity. Anti-citrullinated protein antibodies (ACPA) hallmark the most disease-specific autoimmune response in Rheumatoid Arthritis (RA). Remarkably, ACPA-IgG are heavily N-glycosylated in the variable domain due to somatic mutations that generate abundant N-glycosylation consensus sequences. These sites, obtained from full-length BCR sequences of ACPA-expressing B cells from 12 ACPA-positive RA patients, were here analyzed in detail. Sites that required a single nucleotide mutation to be generated were defined as single somatic hypermutation (s-SHM) sites, whereas sites requiring multiple mutations were defined as m-SHM sites. IgG sequences of 12 healthy donors were used as control. Computational modelling of the germinal center reaction (CLONE algorithm) was used with the germline counterparts of ACPA-IgG heavy chain (HC) sequences to simulate the germinal center response. Our analyses revealed an abundance of N-glycosylation sites in ACPA-IgG HC that frequently required multiple mutations and predominated in specific positions. Based on these data, and taking into account recent insights into the dynamics of the ACPA-response during disease development, we here discuss the hypothesis that N-glycosylation sites in ACPA-IgG variable domains could lead to alternative, possibly antibody affinity-independent selection forces. Presumably, this occurs during germinal center responses allowing these B cells to escape from putative tolerance checkpoints, thereby driving autoreactive B cell development in the pathogenesis of RA.